Clean to dirty limit and Tc suppression in NdFeAsO0.7F0.3 studied by Hc2 analysis. (14th February 2018) - Pallecchi, I; Tarantini, C; Shen, Y; Singh, R K; Newman, N; Cheng, P; Jia, Y; Wen, H-H; Putti, M
Abstract: In this work, we investigate the temperature dependence of the upper critical field, d H c2 /d T, in an increasingly disordered NdFeAsO0.7 F0.3 (NdFeAs(O, F)) single crystal that has been progressively irradiated up to a 5.25 × 10 16 cm − 2 total α -particle dose. For the H ∣∣ ab -plane, d H c2 /d T does not vary remarkably with irradiation, while for the H ∣∣ c -axis it increases sharply after the first irradiation of 3.60 × 10 15 cm −2 and then more gradually with further irradiation doses. Focusing on the H ∣∣ c -axis, we develop a phenomenological analysis of the H c2 slope which allows us to inspect the crossover from the clean to the dirty regime. From the H c2 slope normalized to the critical temperature and to its clean limit value, we extract the ratio of the coherence length ξ BCS to the mean free path ℓ and we find that when T c is reduced by a factor of four from its pristine value, ξ BCS / ℓ becomes as large as ∼7 and ℓ reaches values of ∼1.8 nm, indicating that NdFeAs(O, F) is well into the dirty regime. Our analysis of the H c2 slope also allows us to compare the pair-breaking effectiveness of scattering in different superconductors, showing similarity between unconventional NdFeAs(O, F) and moderate- T c phonon-mediated devices, such as MgB2 and A15 compounds, but much a stronger difference with YBa2 Cu3 O7- δ . This work thus shows that d H c2 /d T is a reliable parameter, providing an alternative to residual resistivity, for investigating the pair-breaking mechanism induced by impurity scattering in superconductors.